Datafication and the role of schooling: challenging the status quo - Eynon, R (Taylor & Francis, 2022)
The increasing use of digital trace data has significant implications for understanding the purposes of education. This chapter begins by provides an overview of some of the key features of the datafication of education. It then examines how the use of digital trace data is influencing the central roles of schools, drawing on the work of Gert Biesta, and highlights how the current use of such data is likely to compound existing inequalities. The chapter then provides a brief account of current responses to digital trace data both within and outside education and argues that these are inadequate. The final part of the chapter argues for the need to reconfigure data use in schools via digital literacy and participatory design to help to challenge the status quo.